Cardioprotective Effect of Polydatin on Ventricular Remodeling after Myocardial Infarction in Coronary Artery Ligation Rats - Gao, Yan; Gao, Jianping; Chen, Changxun; Wang, Huilin; Guo, Juan; Wu, Rong (Planta Medica, 2015)
The purpose of this study was to explore the effect of polydatin on ventricular remodeling after myocardial infarction in coronary artery ligation rats and to elucidate the underlying mechanisms. A rat model of ventricular remodeling after myocardial infarction was established by left coronary artery ligation. Rats with coronary artery ligation were randomly divided into five groups: control, plus 40 mg/kg captopril, plus 25 mg/kg polydatin, plus 50 mg/kg polydatin, and plus 100 mg/kg polydatin. The sham-operated group was used as a negative control. Rats were administered intragastrically with the corresponding drugs or drinking water for seven weeks. At the end of the treatment, the left ventricular weight index and heart weight index were assessed. The cross-sectional size of cardiomyocytes was measured by staining myocardium tissue with hematoxylin and eosin. Collagen content was counted by Sirius red in aqueous saturated picric acid. The concentrations of angiotensin I, angiotensin II, aldosterone, and endothelin 1 in myocardium or serum were determined by radioimmunoassay. Hydroxyproline and nitric oxide concentrations and glutathione peroxidase and catalase activities in serum were measured by ultraviolet spectrophotometry. Our results showed that seven weeks of polydatin treatment resulted in a significantly reduced left ventricular weight index, heart weight index, serum concentrations of hydroxyproline and aldosterone, an increased concentration of nitric oxide as well as enhanced activities of glutathione peroxidase and catalase. Myocardial angiotensin I, angiotensin II, and endothelin 1 levels were also reduced. The cardiomyocyte cross-sectional area and collagen deposition diminished. This study suggests that polydatin may attenuate ventricular remodeling after myocardial infarction in coronary artery ligation rats through restricting the excessive activation of the renin-angiotensin-aldosterone system and inhibiting peroxidation.
Keywords: polydatin; myocardial infarction; ventricular remodeling; coronary artery ligation; renin-angiotensin-aldosterone system; peroxidation